An investigation into possible causes of, and diagnostics for, Alpha Gal Syndrome - Stancic, Jessica Courtney (My University, 2025)
Alpha Gal Syndrome (AGS) is an allergic response to red meat, specifically to a glycan, galactose-[alpha]-1,3-galactose ([alpha]Gal) in mammalian meats. AGS develops after tick bites, mainly from the lone star tick, Amblyomma americanum, which is commonly found in the Central and Southeastern United States. Diagnosing AGS is not straightforward and relies on a combination of symptoms, patient history, and a blood test. The only current diagnostic tool for AGS is measuring the amount of specific Immunoglobulin E anti-[alpha]Gal (sIgE anti-[alpha]Gal); AGS is diagnosed with the diagnostic threshold of ≥0.1 IU/mL. [alpha]Gal is a sugar located on the terminal ends of glycans found in many glycolipids and glycoproteins of most mammals except for humans and Old world primates. However, healthy individuals without AGS are often found to have high levels of sIgE anti-[alpha]Gal (false positive tests) and a substantial proportion of individuals diagnosed with AGS do not meet the diagnostic threshold at sIgE anti-[alpha]Gal ≥0.1 IU/mL (false negative tests). As such, accurate diagnoses for AGS can be challenging and modifications to the current testing protocols are urgently needed. Although AGS is induced by tick bites, less than 10% of individuals bitten by the lone star tick will develop AGS. This variation in response to tick bites may arise from the differences in the potency of AGS sensitizers among tick populations, or from individual variation in innate sensitivity. We aim to understand this variation in responses to tick-mediated AGS sensitization, as well as to identify new potential targets for AGS diagnostic markers. For chapter 1, we hypothesized that low levels of alpha-galactosidase activity were associated with AGS. Enzymatic degradation of [alpha]Gal may protect immune systems during the sensitization and elicitation steps of AGS. We suspect that low levels of alpha-galactosidase activity may be part of the mechanism involved in the manifestation of AGS symptoms, which may make it a good potential diagnostic marker for AGS. To test our hypothesis, we obtained 51 plasma samples from a population diagnosed with AGS and 102 control samples. We first measured the levels of plasma sIgE anti-[alpha]Gal in AGS and control samples using an anti-[alpha]Gal IgE detection ELISA (enzyme-linked immunosorbent assay). We confirmed that most of our AGS patient plasma samples had elevated levels of anti-[alpha]Gal IgE with 80 % sensitivity and 80% specificity, which correlates with the general consensus seen in the literature. We also measured plasma alpha-galactosidase activity levels using a fluorescence substrate assay. The assay measured the amount of galactose removed from 4-Mu-Gal (4-Methylumbelliferyl-[alpha]-D-galactopyranoside). The total fluorescence of 4-Mu released from 4-Mu-Gal provides quantifiable alpha-galactosidase activity measurements over a given time period. We discovered that alpha-galactosidase activity is significantly lower in AGS samples. To confirm the validity of this result, given we utilized two different sample cohorts, we performed a series of freeze-thaw experiments to test our sample stability with different storage conditions. We found that alpha-galactosidase activity in plasma remains unaffected up to 6 freeze-thaw cycles, the maximum number we have tested so far. Additionally, we tested for correlation between the length of the AGS sample storage time and alpha-galactosidase activity and found no correlation. Therefore, we conclude that lower alpha-galactosidase activity is correlated with AGS, implying that the immune systems of AGS individuals may be exposed to greater levels of [alpha]Gal. Conversely, we conclude that the higher alpha-galactosidase activity present in AGS-tolerant individuals may protect the immune system from developing an allergic response to [alpha]Gal. For chapter 2, we hypothesized that differences in the amounts of the proteins alpha-galactosidase A (GLA) and/or alpha-N-acetylgalactosaminidase (NAGA) were responsible for the significantly reduced alpha-galactosidase activity seen in AGS samples. In order to identify the causal factor for the low alpha-galactosidase activity, we measured the amount of immunoreactive proteins (GLA or NAGA) by using sandwich ELISAs. We found that NAGA levels are significantly lower in AGS samples, but that there is no difference in GLA levels between AGS and control samples. We also found that NAGA level, but not GLA level, is correlated with alpha-galactosidase activity in plasma. Thus, it appears that NAGA is likely responsible for alpha-galactosidase activity observed in plasma. Our results support the hypothesis that alpha-galactosidase is involved in the manifestation of, or tolerance to, AGS. We suspect that the breakdown of [alpha]Gal may play an important role in the AGS sensitization and/or elicitation steps. In addition, we also demonstrated that NAGA levels in plasma are associated with alpha-galactosidase activity in plasma. This study suggests that alpha-galactosidase activity and NAGA level may be useful as diagnostic tools to add to the current AGS diagnostic method, the sIgE anti-[alpha]Gal antibody test. The combination of all three tests provides a significantly improved specificity and sensitivity for AGS diagnostics.
Keywords: Alpha Gal Syndrome; Alpha-galactosidase A; Alpha-N-acetylgalactosaminidase; Alpha-galactose